Monitoring T-Cell Responses in Translational Studies: Optimization of Dye-Based Proliferation Assay for Evaluation of Antigen-Specific Responses - Ten Brinke, Anja; Marek-Trzonkowska, Natalia; Mansilla, Maria J.; Turksma, Annelies W.; Piekarska, Karolina; Iwaszkiewicz-Grześ, Dorota; Passerini, Laura; Locafaro, Grazia; Puñet-Ortiz, Joan; van Ham, S. Marieke; Hernandez-Fuentes, Maria P.; Martínez-Cáceres, Eva M.; et al. (Frontiers in Immunology, 2017)
Adoptive therapy with regulatory T cells or tolerance-inducing antigen presenting cells are innovative and promising therapeutic approaches to control undesired and harmful activation of the immune system, as observed in autoimmune diseases, solid organ and bone marrow transplantation. One of the critical issues to elucidate the mechanisms responsible for success or failure of these therapies and define the specificity of the therapy is the evaluation of the antigen (Ag)-specific T cell responses. Several efforts have been made to develop suitable and reproducible assays. Here, we focus on dye-based proliferation assays. We highlight with practical examples the fundamental issues to take into consideration for implementation of an effective and sensitive dye-based proliferation assay to monitor Ag-specific responses in patients. The most critical points were used to design a road-map to set up and analyze the optimal assay to assess Ag-specific T cell responses in patients undergoing different treatments. This is the first step to optimize monitoring of tolerance induction, allowing comparison of outcomes of different clinical studies. The road-map can also be applied to other therapeutic interventions, not limited to tolerance induction therapies, in which Ag-specific T cell responses are relevant like vaccination approaches or cancer immunotherapy.